The perinatal period should be considered in neonatal acute respiratory distress syndrome: comparison of the Montreux definition vs. the second pediatric acute lung injury consensus conference definition - Liu, Liting; Zhang, Yihan; Wang, Yiran; He, Yu; Ding, Xionghui; Chen, Long; Shi, Yuan (Frontiers in Pediatrics, 2023)
Background: The recently developed Montreux definition for neonatal acute respiratory distress syndrome (ARDS) partially differs from the Second Pediatric Acute Lung Injury Consensus Conference (PALICC-2) definition. Here, we compare the Montreux and PALICC-2 definitions regarding morbidity, mortality, and prognosis of neonatal cases of ARDS in order to evaluate which definition is more appropriate for newborns. Methods: Neonates admitted to our neonatal intensive care unit between 1 January 2018 and 30 September 2019 who met the Montreux or PALICC-2 definition of neonatal ARDS were retrospectively analyzed (n = 472). One comparison was made between application of the Montreux and PALICC-2 definitions to neonates outside the perinatal period (> 7 d after birth). A second comparison was made between a diagnosis of neonatal ARDS within (≤ 7 d of birth) and outside (> 7 d after birth) the perinatal period using the Montreux definition. Results: No significant differences in morbidity, mortality, severity, therapies, or prognosis were observed between neonates in the extra perinatal group according to the Montreux and PALICC-2 definitions. However, epidemiology, clinical course, and prognosis of neonatal ARDS within the perinatal period did differ from those outside the perinatal period according to the Montreux definition. Conclusion: Neonates with ARDS within the perinatal period have unique triggers, epidemiology, clinical course, and prognosis, yet a similar pathobiology pattern, to neonates at other ages. Therefore, it may be essential to consider the perinatal period when defining neonatal ARDS.